2020
DOI: 10.1017/s0022377820001440
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of fishbone cycle on energetic particle intensity in EAST low-magnetic-shear plasmas

Abstract: The dependence of fishbone cycle on energetic particle intensity has been investigated in EAST low-magnetic-shear plasmas. It is observed that the fishbone mode growth rate, saturation amplitude as well as fishbone cycle frequency clearly increase with increasing neutral beam injection (NBI) power. Moreover, enhanced electron density and temperature perturbations as well as energetic particle loss were observed with greater injected NBI power. Simulation results using M3D-K code show that as the NBI power incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…1984; Zhu et al. 2020), (2.1) and (2.2). It is shown that there are only five free parameters in this model, , , , and .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…1984; Zhu et al. 2020), (2.1) and (2.2). It is shown that there are only five free parameters in this model, , , , and .…”
Section: Discussionmentioning
confidence: 96%
“…1984; Zhu et al. 2020), where is the average trapped EP beta within the surface, is fishbone amplitude (, the normalised radial perturbed magnetic field), is the deposition rate of trapped EP within the surface, is a measure of the EP loss rate, , , is the fraction of trapped EPs that can be ejected, is the excitation threshold of fishbone, is the resonant drive of trapped EPs and is Heaviside function. The evolution of is periodic with minimum and maximum .…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The energetic particles profile in three typical time slices calculated by TRANSP-NUBEAM [45,46] code in shown in figure 11(e). In these times, the corresponding energetic trapped particle pressure ratio (β ep ) are 0.13%, 0.18% and 0.21% [47]. Shorter intervals between two adjoined fishbones indicate that the state tends to be stable, and the corresponding q profile quickly recovers to the initial state.…”
mentioning
confidence: 99%